Making sense of sustainability and drivers for organising sustainability in business: an exploratory study in Malaysia - Ponnusamy, Vanitha (2024)
This study is on sustainability in Malaysia, whereby there is a transition from CSR to Sustainability nationwide. The formation of Business Council for Sustainability and Responsibility Malaysia (BCSRM) supported the practice for sustainability in Malaysia. Along with Securities Commission and Bursa Saham, sustainability was developed and enhanced in Malaysia. However, there is a curiosity and interest on how sustainability is perceived and implemented. There are many guidelines and toolkits developed, but to what extend is this being embraced and followed remain to be an interest. As this takes an interpretive approach, it will be attractive to know whether there is a unanimous understanding, or it differs when it is deemed suitable for the nature of their respective business. Extending that, drivers for sustainability is delved into, specifically institutional due to literature significance. Subsequently, an enquiry is made on how sustainability is organised, as it is instrumental for practice. Therefore, a qualitative study was planned and executed, whereby 30 interviews were conducted. The respondents are practitioners of sustainability in their company, and they were selected using purposive sampling. There was a wide spread of industry so as to give a more diverse range of answers. Each interview lasted between 45 to 60 minutes and was transcribed; and analysed using a combination of thematic and sensemaking approach. A framework for this study was adapted from Jackson 2010 who had previously adapted from 3 different studies on sensemaking.